2012
DOI: 10.1111/j.1538-7836.2012.04679.x
|View full text |Cite
|
Sign up to set email alerts
|

A high affinity, antidote‐controllable prothrombin and thrombin‐binding RNA aptamer inhibits thrombin generation and thrombin activity

Abstract: Background The conversion of prothrombin to thrombin is one of two non-duplicated enzymatic reactions during coagulation. Thrombin has long been considered an optimal anticoagulant target because it plays a crucial role in fibrin clot formation by catalyzing the cleavage of fibrinogen, upstream coagulation cofactors, and platelet receptors. Although a number of anti-thrombin therapeutics exist, it is challenging to use them clinically due to their propensity to induce bleeding. Previously, we isolated a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 47 publications
2
73
0
Order By: Relevance
“…We have employed this selection method to generate modified RNA aptamers to activated coagulation factor VII (FVIIa) (Layzer and Sullenger, 2007), activated factor IX (FIXa) (Rusconi, et al, 2002), activated factor X (FXa) (Buddai, et al, 2010), and prothrombin (Layzer and Sullenger, 2007). All of the aptamers bind to both the zymogen and enzyme form of their target protein ( e.g., FVII and FVIIa), and mechanistic studies with the FIXa, FXa, and prothrombin aptamers indicate that the aptamers bind a large surface area on the zymogen/enzyme that is critical for procoagulant protein-protein interactions (Bompiani, et al, 2012; Buddai, et al, 2010; Sullenger, et al, 2012). Moreover, we have pioneered the development of two independent types of antidotes that can rapidly modulate aptamer anticoagulant function (Oney, et al, 2009; Rusconi, et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…We have employed this selection method to generate modified RNA aptamers to activated coagulation factor VII (FVIIa) (Layzer and Sullenger, 2007), activated factor IX (FIXa) (Rusconi, et al, 2002), activated factor X (FXa) (Buddai, et al, 2010), and prothrombin (Layzer and Sullenger, 2007). All of the aptamers bind to both the zymogen and enzyme form of their target protein ( e.g., FVII and FVIIa), and mechanistic studies with the FIXa, FXa, and prothrombin aptamers indicate that the aptamers bind a large surface area on the zymogen/enzyme that is critical for procoagulant protein-protein interactions (Bompiani, et al, 2012; Buddai, et al, 2010; Sullenger, et al, 2012). Moreover, we have pioneered the development of two independent types of antidotes that can rapidly modulate aptamer anticoagulant function (Oney, et al, 2009; Rusconi, et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of this approach has been confirmed by experiments on animal models. An aptamer was delivered into the bloodstream and exhibited a therapeutic effect, while subsequent injection of an antidote inactivated the aptamer and stopped its action [41, 42]. The high efficiency of aptamer hybridization with an antidote in blood provides a unique opportunity to control the duration of the therapeutic action.…”
Section: Limitations In Aptamer Application and Possible Sol Utionsmentioning
confidence: 99%
“…fibrin clot formation, feedback activity and platelet activation). The complementary oligonucleotide antidote can rapidly (b2 min) and durably (>2 h) reverse the aptamer anticoagulation in vitro (Bompiani et al, 2012). Many research groups recently demonstrated that, among the thrombin inhibitors, the aptamers TBA 15 , TBA 29 , and a series of related modified derivatives, were effectively controllable in their anticoagulation activity adopting various methodologies, such as the use of porphyrins, of complementary oligonucleotides or of external stimuli (light or radiofrequency irradiations).…”
Section: Modulation Of Aptamers Activitymentioning
confidence: 99%